The Effect of Concomitant Proton Pump Inhibitor and Cabozantinib on the Outcomes of Patients with Metastatic Renal Cell Carcinoma. (25th February 2021) - Rassy, Elie; Cerbone, Luigi; Auclin, Edouard; Benchimoll‐Zouari, Axelle; Flippot, Ronan; Alves Costa Silva, Carolina; Colomba, Emeline; Geraud, Arthur; Guida, Annalisa; Mir, Olivier; Combarel, David; Paci, Angelo; et al.
Abstract: Introduction: Cabozantinib is an oral tyrosine kinase inhibitor that is approved for the treatment of metastatic renal cell carcinoma (mRCC). Cabozantinib is a weak base that exhibits a pH‐dependent solubility profile in vitro which raises concerns about its bioavailability in patients treated with proton pump inhibitors (PPIs). The purpose of this study was to investigate whether PPI use has an impact on the efficacy, safety, and residual concentration (Ctrough) of cabozantinib in patients with mRCC. Materials and Methods: This is a retrospective review of a prospectively collected electronic database of patients with mRCC who received cabozantinib at Gustave Roussy between February 2014 and December 2018. The Kaplan‐Meier method was used for survival analysis and the Cox proportional‐hazard model for uni‐ and multivariate analysis. In parallel, we conducted a pharmacokinetic study of cabozantinib in a distinct cohort of 50 mRCC patients, in which cabozantinib Ctrough was assayed using a validated tandem mass spectrometry–liquid chromatography method. Results: We identified 99 patients treated with cabozantinib, including 43 patients being PPI users. With a median follow‐up of 30.3 months, PPI users showed similar progression‐free survival and overall survival outcomes compared with PPI nonusers. Similarly, the incidence of adverse events was not significantly different between the PPI users and nonusers, although PPI users required dose reductions more often. In the independent pharmacokinetic cohort, of whom 21 received PPI concomitantly, Ctrough was similar between the two groups. Conclusion: In line with the pharmacologic data, the concomitant use of PPI does not significantly impact the efficacy or safety of cabozantinib in patients with mRCC. Implications for Practice: Drug interactions, especially between targeted therapies and proton pump inhibitors (PPI), were shown to potentially impact the outcomes of cancer patients. Cabozantinib, a current therapeutic standard in metastatic renal cell carcinoma (mRCC), exhibits a pH‐dependent solubility profile, which raises concerns about its bioavailability in patients treated with proton pump inhibitors (PPI). At the present time, there is no evidence regarding the effect of PPIs on cabozantinib's efficacy and safety in patients with mRCC. This study found that the concomitant use of PPI during cabozantinib treatment in mRCC patients does not appear to impact the residual concentration, efficacy, and safety of cabozantinib in a real‐life context. Abstract : This article reports on the effect of proton pump inhibitors on the pharmacology, efficacy and safety outcomes of patients with metastatic renal cell carcinoma treated with cabozantinib.